Implementasi Modul Pembelajaran Fisika Berbasis Kearifan Lokal Untuk Meningkatan Hasil Belajar Dan Respon Peserta Didik Pada Materi Gelombang Bunyi - Yosefa Lama Uran; Isabel Coryunitha Panis; Maria Ursula Jawa Mukin (MAGNETON: Jurnal Inovasi Pembelajaran Fisika UNWIRA, 2024)
This research aims (1) to determine the feasibility of a module based on local wisdom on sound wave material in increasing students' conceptual understanding (2) to determine the increase in student learning outcomes in applying the sound wave material module based on local wisdom. The population and sample in this study were students in class XI Science at Sint Carolus Catholic High School on Sound Waves material. This research uses a development method (Research & Development Design). The research stages of this research are (1) Research and Data Collection; (2) Planning; (3) Product Draft Development; (4) Initial Field Trials; (5) Revising Trial Results (6) Field Trials. The instruments used are test questions, validation sheets and student response questionnaires. The data analysis technique used is quantitative descriptive analysis technique. The results of this research show that the results of module validation by 4 expert validators with an average percentage of all aspects are 88.18% with the category very suitable for use. The N-Gain value was obtained at 79.40 in the effective category and an average of 70.41% was obtained in the practical product category. The conclusion in this research is that the Physics Module Based on Local Wisdom on Traditional Musical Instruments was developed practically so that it can be used as a learning resource in learning at Sint Carolus Catholic High School.